TASK-BASED INSTRUCTION IN TEACHING SPEAKING SKILL: TASK-BASED INSTRUCTION IN TEACHING SPEAKING SKILL - Z. Elmuratova, Z. Elmuratova (Журнал иностранных языков и лингвистики, 2025)
Speaking is considered as the most important language skill because speech is used more often than writing in everyday life and it has a great importance in language development of learners’ proficiency. Learners have to obtain four speaking skills in order to use the spoken language effectively: -Accuracy: Accuracy involves skill of using grammar, vocabulary and pronunciation (intonation, stress, rhythm) correctly to express various ideas.